Plants as a cost‐effective source for customizable photosynthetic wound dressings: A proof of concept study - González Itier, Sergio.; Miranda Cárdenas, Miguel Ángel.; Corrales Orovio, Rocío.; Vera, Constanza; Veloso Giménez, Valentina.; Cárdenas Calderón, Camila.; Egaña, José Tomás (John Wiley and Sons, 2024)
Oxygen is essential for tissue regeneration, playing a crucial role in several processes, including cell metabolism and immune response. Therefore, the delivery of oxygen to wounds is an active field of research, and recent studies have highlighted the potential use of photosynthetic biomaterials as alternative oxygenation approach. However, while plants have traditionally been used to enhance tissue regeneration, their potential to produce and deliver local oxygen to wounds has not yet been explored. Hence, in this work we studied the oxygen-releasing capacity of Marchantia polymorpha explants, showing their capacity to release oxygen under different illumination settings and temperatures. Moreover, co-culture experiments revealed that the presence of these explants had no adverse effects on the viability and morphology of fibroblasts in vitro, nor on the viability of zebrafish larvae in vivo. Furthermore, oxygraphy assays demonstrate that these explants could fulfill the oxygen metabolic requirements of zebrafish larvae and freshly isolated skin biopsies ex vivo. Finally, the biocompatibility of explants was confirmed through a human skin irritation test conducted in healthy volunteers following the ISO-10993-10-2010. This proof-of-concept study provides valuable scientific insights, proposing the potential use of freshly isolated plants as biocompatible low-cost oxygen delivery systems for wound healing and tissue regeneration.
Keywords: Marchantia polymorpha; Photosynthetic biomaterial; Oxígeno; Cicatrización de heridas